Care in the time of COVID: An interpretative phenomenological analysis of the impact of COVID-19 control measures on post-partum mothers’ experiences of pregnancy, birth and the health system - von Rieben, Mikhayl A.; Boyd, Leanne; Sheen, Jade (Frontiers in Psychology, 2022)
Background: Findings suggest pandemic control measures have modified maternal health practices, compromising the quality of care provided to new and expectant mothers and interfering with their birthing experiences. For this reason, this study explored the lived experiences of post-partum Victorian mothers during the pandemic as well as the potential influence of control measures over their perceptions regarding the health system. Methods: This study used a qualitative approach. Recruitment was conducted between May and June 2021, using both the Australian Breastfeeding Association’s social media pages and snowball recruitment. Interviews were semi-structured using open-ended questions relating to key themes. Seven Victorian post-partum mothers were identified and their transcripts analysed using Interpretative Phenomenological Analysis. Results: Mothers described how unexpected changes to maternal care exacerbated feelings of uncertainty regarding pregnancy and birth. Mothers also differentiated between impacts by the health system and the role healthcare professionals played in moderating these effects. Whilst visitor restrictions provided some benefit, restrictions to familial and social support left many of the mothers feeling alone during their pregnancy and interfered with their immediate post-partum experience. Conclusions: This study illustrates the importance of evidence-based practice in maternal care and provides insights for both health professionals and policy analysts in developing new or modifying existing guidelines that better balance the needs of expectant and post-partum mothers with pandemic control measures.